Project Performance Analysis Using the Earned Value Management (EVM) Method (Case Study: PT XYZ) - Akhmad Ittang Anwarsyah; Ervina Ahyudanari (IPTEK Journal of Proceedings Series, 2019)
The development of the construction in Indonesia is growing rapidly over time, along with rapid economic growth. In its implementation, many projects have problems with work delays so that the project completion is not in accordance with the scheduled time and results in increased costs due to additional completion time. This delay puts the contractor to do a re-planning or commonly referred to as a re-baseline. The inaccuracy of re-planning can have an impact on not achieving revenue targets and having a commercial impact on the construction company. a project performance analysis is needed to anticipate these problems as early as possible. The method used to analyze project performance with a review of the implementation time and budget to manage the dynamics that occur is to use the Earned Value Management method. EVM is a method that is used to determine the progress of a project greater or smaller than the budgeted budget and faster or slower than a predetermined schedule. This study shows that EVM parameters, namely SPI and CPI on 3 PT Projects. XYZ shows both in the field of work (SPI) or budget planning (CPI), PT. XYZ still shows a performance that is not good enough. Whereas EVM Analysis on 3 XYZ Projects shows that the cost requirements needed for project completion are above the budget. The Sugar Factory EPCC Project A based on EVM will require 107% of the BAC value for completion of work, the EVM-based Cooking Plant Construction Project will require 110% BAC for completion of work and the Sugar Factory EPCC Project B based on EVM will require 106% BAC to complete the work. Referring to the EAC calculation and risk mitigation for the costs needed, the Project for the Construction of Edible Oil Plants has the greatest potential to be able to reduce business yields. Through EVM, it was also found that the time for implementing the three projects increased from the duration of the initial planning. The EPCC Project for Sugar A Factory increased for 6 Months, the Cooking Oil Plant Construction Project increased for 5 months and the EPCC Sugar Factory B Project increased for 2 months.